Analysis Of Comparison Of Cost And Time Implementation Of Road Projects Using Methods Time Cost Trade Off: (Case Study : Napoleon Road “Rumah Apung” Bangsring Village, Wongsorejo District, Banyuwangi Regency) - Suciati Puji Rahayu; M ikhsan Setiawan (Journal of World Conference (JWC), 2020)
Maintenance project Napoleon road “Rumah Apung” in bangsring village of Wongsorejo subdistrict Banyuwangi. In the implementation of this project there were delays in some jobs, namely ordinary excavation, pavement exavation is paved without cold milling machine, and fc’ 25 Mpa quality concrete. So that it can affect other activities. One way to anticipate delays is by accelerating using the Time Cost Trade Off method, through alternative hours of work (overtime) for 3 hours on the first 3 days of work and the addition of labor for the first 3 days of work commenced. The result of the analysis of the two alternatives in this study obtained results for ordinary excavations with the addition of working hours (overtime) for 3 hours in the first three days of work started to obtain project cost efficiency of Rp. 5.537.232,- from the normal cost of Rp. 6.523.171,20,- compared to the addition of labor. Whereas paved pavement excavations without cold milling machines have a 9 day efficiency period from the normal duration of 12 working days and a cost efficiency of Rp. 2.412.000,- from the normal cost of Rp. 3.216.000,- compared to the additional hours of overtime work. For fc’ 25 Mpa quality concrete work, efficiency at normal project costs and time is 12 working days with normal costs Rp. 3.040.950,816,- in addition to working hours (overtime).